Ziemia międzyrzecka w prasie ziomkowskiej po 1945 roku = The Międzyrzecz Land in the German press after 1945 - Czabańska-Rosada, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Published since 1949, "Heimatgruss" a magazine of former German inhabitants of Kreis Meseritz, contains many reports about postwar reality of the Międzyrzecz region. First direct reports started to be published in 1954, and were written down by the few Germans who travelled the motherland lost in 1945. Broader reports have been published since 1995, when Heimatkreis Meseritz association started official cooperation with regions authorities. In 2003 for the first time there appeared a section "From the Polish press", which became a constant element of the magazine. In this section there are abstracts of information from the local press, television, websites and also reports from the experienced events. This section offers broad spectrum of social, economical, political, cultural and religious events overview. Furthermore, there appear commentaries and presentations of region-centered publications. Alongside the paper issue, these reports are posted in electronic form on Heimatkreis website. To the present this section appeared in 44 issues out of 211, which is 20% of all issues since the first publication. It means that 20% ofall "Heimatgruss" publications contain reliable information about Międzyrzecz region. Editorial office does not limit the information, and sometimes they take up to 1/5 of the whole issue. It concludes that readers of "Heimatgruss" are actively interested in the current events in their former motherland. Letters from the readers and comments on the website are also the evidence of this phenomenon. A generational change, which happened both in Heimatkreis Meseritz administration and editorial office of "Heimatgruss", resulted in increased interest in present day affairs of former motherland. Younger generation has been going on many tours in the Międzyrzecz region, and in different parts of Poland, beginning a dialogue with Polish inhabitants.
Keywords: prasa; prasa niemiecka; Ziemia Międzyrzecka; Międzyrzecz; press; german press; Międzyrzecz Land